Assay Of Detoxification Potential Of DL-Methionine On Dietary Gliricidia Leaf Meal In Rabbit Nutrition: Relative Organ Weight And Blood Indices - EDOH, JOHANNES HUGUES; ANNONGU, AMOS AZOR; HOUNDONOUGBO, M. FRÉDÉRIC; HOUNDONOUGBO, PASCAL VENANT; AJIDE, SOLOMON O (My University, 2019)
An investigation on the detoxification potential of DL-Methionine on Gliricidia Leaf Meal (GLM) was performed. Gliricidia sepium leaves were dried and milled into meal (GLM) and incorporated in diets at 0% (F0, control), 10% (F10) and 15% (F15) raw and at 10% (F SM 10) and 15% (F SM 15) with 0.3% DL-methionine supplementation. 60-weaned rabbits (of 49-days old) averaging 1066±16.3 g/rabbit were used as test animal models and fed the 5-diets to appetite over a feeding trial lasting 42-days. At the age of 91±2 days, 4-rabbits were sampled per treatment for internal organ weight and three (3) for haematological and biochemical studies. Dietary treatment gave no significant differences (p>0.05) for all the relative organ weights (liver, kidneys, heart and spleen) but the lungs (p<0.05). Haematological parameters such as PCV, RBC as well as MCH, MCV and MCHC were not significantly affected by the dietary treatment (P>0.05) while WBC counts decreased in diets F SM 10, F15 and F SM 15. The biochemical determinants (glucose, albumin, globulin, ALT, ALP, Na + , P, Mg 2+ ,Cl-, HCO 3-) measured on the rabbits fed the test diets were comparable to those fed the conventional diets (p>0.05). Diet F15 significantly increased AST enzyme (p<0.05) while ALT value was significantly augmented (p<0.05) in all the experimental treatments compared to the control diet. Besides, methionine supplementation in diet FSM10 and FSM15 reduced ALT activities compared to methionine unsupplemented diets F10 and F15 respectively. However, this latter was not statistically significant (p>0.05). Dietary leaf meal of G. sepium with or without methionine treatment had no significant effect (p>0.05) on blood concentration of sodium (Na +), phosphorus (P), magnesium (Mg 2+), chloride and bicarbonate ions (HCO 3-). Calcium electrolyte was increased (p<0.05) with dietary treatments compared to the conventional diet (F0). In summary, GLM at level up to15% in diets had no adverse effects on internal organs status, haematological parameters, some biochemical determinants and electrolyte profile of growing rabbits. Elevation in serum ALT and AST suggested that antinutrients in GLM elicited mild tissue lesions in rabbit which is slightly corrected by methionine supplementation. It is recommended that in subsequent researches, methionine supplementation, to facilitate detoxification, should include other detoxicant like Choline chloride and Polyethylene Glycol (PEG).
Keywords: Blood indices; detoxification; GLM; methionine; organ weight; rabbit